Analysis on the crown convergence deformation of surrounding rock for double-shield TBM tunnel based on advance borehole monitoring and inversion analysis. (September 2020) - Li, Chaoyi; Hou, Shaokang; Liu, Yaoru; Qin, Pengxiang; Jin, Feng; Yang, Qiang
Highlights: A convergence deformation prediction method for double-shield tunnels is proposed. Deformation is monitored by advance borehole and a measuring tube with FBG sensors. Constitutive parameters are obtained by inversion of deformation monitoring data. Errors caused by reference point displacement are corrected by numerical model. Abstract: The surrounding rock deformation during tunnelling is difficult to be measured or calculated accurately, especially in tunnels constructed by double-shield TBM. A method for prediction of the crown convergence deformation of surrounding rock based on advance borehole monitoring and numerical inversion analysis is proposed. Combined with the field deformation monitoring and numerical simulation, the final crown convergence deformation of surrounding rock is obtained. When TBM advances to the test section, the horizontal directional drilling machine is used to drill an advance borehole at the top of tunnel and 1.6 m away from the tunnel face, and the measuring tube with fiber Bragg grating (FBG) sensors has been installed in the borehole to conduct the deformation monitoring. Then, based on the numerical simulation with the viscoplastic creep constitutive model, the final crown deformation of surrounding rock during TBM tunneling process has been predicted, in which the parameters of surrounding rock are obtained through the inversion analysis of deformation data and the error caused by the displacement of reference point has been corrected. The surrounding rock crown convergence deformation was also estimated by using a scaled instrument in the grout hole of lining segment and is approximately the same with the above predicted value, which show that the proposed method can well analyze the surrounding rock crown convergence deformation during tunneling for double-shield TBM tunnels.